Dictionary of British Arms Medieval Ordinary : Volume Three - Flower, Sarah; Woodcock, Thomas (Dictionary of British Arms, 2009)
This is the third of a four-volume collection of British heraldic arms, arranged alphabetically according to their designs and covering the period before 1530. Listed in this volume are entries from Chief to Fess. This book will help readers to identify the arms that were widely displayed in the Middle Ages and which can now be found not only on tombs, monuments and seals, but also on textiles, manuscripts, metalwork, glass, wall paintings, and other medieval artefacts. The index allows even those without any specialist knowledge of the subject to discover the blazons of arms recorded for particular surnames in the medieval period. Produced specifically to enable readers to identify individual coats of arms, it is an invaluable reference for historians, antiquaries, archaeologists, genealogists and those dealing in and collecting medieval objects.